If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 2(x + -12) = -2(1 + -4x) Reorder the terms: 8x + 2(-12 + x) = -2(1 + -4x) 8x + (-12 * 2 + x * 2) = -2(1 + -4x) 8x + (-24 + 2x) = -2(1 + -4x) Reorder the terms: -24 + 8x + 2x = -2(1 + -4x) Combine like terms: 8x + 2x = 10x -24 + 10x = -2(1 + -4x) -24 + 10x = (1 * -2 + -4x * -2) -24 + 10x = (-2 + 8x) Solving -24 + 10x = -2 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -24 + 10x + -8x = -2 + 8x + -8x Combine like terms: 10x + -8x = 2x -24 + 2x = -2 + 8x + -8x Combine like terms: 8x + -8x = 0 -24 + 2x = -2 + 0 -24 + 2x = -2 Add '24' to each side of the equation. -24 + 24 + 2x = -2 + 24 Combine like terms: -24 + 24 = 0 0 + 2x = -2 + 24 2x = -2 + 24 Combine like terms: -2 + 24 = 22 2x = 22 Divide each side by '2'. x = 11 Simplifying x = 11
| 75s=25s+8 | | (8*8*8)-(8*-8*-8*-8*-8*-8)= | | 1.9(-5g+6)-0.3g= | | -67+5x=53-x | | .13=-5f+48 | | 2x+3y-4y= | | F(1)=2x+7 | | 6y+15+3=2y-10 | | v^2+35=12v | | y^2+6y-40= | | v^2-44=0 | | 13=m+9 | | x-12+x=2(x-12)+2(x-12)-4 | | 5x+4y=28-x | | -94+3x=153-10x | | h-15h+4=22.5 | | 4(3x+2)+1=-15 | | 2x^2=30x-100 | | -40+-55-10=-12v+36 | | 15-7=8 | | 9=n+7 | | P+x=8+f+(-f) | | -2x-4y=2x-4 | | -8=-2x-6 | | -98+x=56-10x | | -17-37=26 | | 15-7=x | | 2x-14=x-7 | | 6y+5x=-3 | | -2x+5x^2-7=0 | | -4=t+8 | | -5+33=7 |